Cost–Benefit and Cost–Utility Analysis of Amphotericin B Supplementation of Corneal Storage Media With Endothelial Keratoplasty-Prepared Tissue. Issue 4 (April 2020) - Chiang, Trent Tsun-Kang; Shtein, Roni M.; McCoy, Kristen; Hurlbert, Susan; Grossman, Gregory H.
Abstract : Purpose: To determine the cost-effectiveness of amphotericin B supplementation, we analyzed both current costs to treat postendothelial keratoplasty (EK) fungal infections and potential costs associated with amphotericin B supplementation. Methods: We collected 19 US cases of post-EK fungal eye infections from the published literature and assessed the associated costs from the literature. A survey of surgeons was also conducted with questions regarding their experiences in managing these infections. Results: We estimated that the costs to diagnose, manage, and treat post-EK fungal keratitis and post-EK fungal endophthalmitis are USD 21, 113 and 34, 850, respectively. The largest portion of the costs can be attributed to the need for additional surgical management, which is required in 79% of the cases. We estimated the total cost of amphotericin B supplementation to be 44.39 per graft with use of conventional amphotericin B and conservative assumptions regarding supplementation processes. Cost-effectiveness analysis demonstrated that amphotericin B supplementation is cost-effective at 100, 000 per quality-adjusted life-year level only if amphotericin B supplementation can prevent more than 69.62% of post-EK fungal infections, assuming the incidence of post-EK fungal infection remains at the level it was between 2012 and 2017. Conclusions: We found that amphotericin B supplementation can be cost-effective under conservative assumptions if it is moderately effective in preventing post-EK fungal infections.